Enhancing Elementary Students' Interest and Conceptual Understanding of the Solar System Through Edutainment-Based Interactive Learning Media - Hutri Darmayanti; Havifah Cahyo Khosiyono; Ana Fitrotun Nisa; Berliana Henu Cahyani; Didi Supriyadi (STAI Hubbulwathan Duri, 2025)
Traditional teaching methods in science education often struggle to effectively convey abstract concepts such as the Solar System, leading to low student engagement and limited conceptual understanding. Integrating interactive learning media, particularly edutainment games, offers a promising solution to enhance both interest and comprehension in elementary science learning. This study employed a quasi-experimental design using a Nonequivalent Control Group Design to evaluate the effectiveness of edutainment game-based learning media. Participants included two groups of sixth-grade students: an experimental group taught using edutainment games and a control group taught using conventional methods. Pretest and post-test assessments were administered to measure conceptual understanding, while a Likert-scale questionnaire evaluated students' learning interest. Data were analyzed using Paired Sample T-Tests to determine the significance of differences between pre- and post-intervention scores. Findings revealed a statistically significant improvement in both learning interest and conceptual understanding among students in the experimental group compared to the control group (p 0.001). Students exposed to edutainment game-based learning demonstrated higher engagement levels and deeper comprehension of the Solar System topic. The use of game-based interactive media not only fostered active learning but also addressed challenges associated with teaching abstract scientific content. These results support the integration of edutainment games into elementary science curricula as a means to enhance learning outcomes and student motivation.